2023
DOI: 10.3390/biomedicines11113035
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Analogs, SGLT-2, and DPP-4 Inhibitors: A Triad of Hope for Alzheimer’s Disease Therapy

Magdalena Złotek,
Antonina Kurowska,
Mariola Herbet
et al.

Abstract: Alzheimer’s is a prevalent, progressive neurodegenerative disease marked by cognitive decline and memory loss. The disease’s development involves various pathomechanisms, including amyloid-beta accumulation, neurofibrillary tangles, oxidative stress, inflammation, and mitochondrial dysfunction. Recent research suggests that antidiabetic drugs may enhance neuronal survival and cognitive function in diabetes. Given the well-documented correlation between diabetes and Alzheimer’s disease and the potential shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 255 publications
0
6
0
Order By: Relevance
“…This localized distribution in the hypothalamus is significant as it aligns with the proposed effects of SEM in the brain, such as neuroprotection. These effects are believed to be associated with the interaction of SEM with GLP-1 receptors in the brain [ 64 , 65 , 66 , 67 , 68 ]. This paradoxical finding underscores the complexity of SEM’s interaction with the brain and challenges the conventional understanding of its BBB permeability.…”
Section: Sem Pharmacokinetics In Animal Modelsmentioning
confidence: 99%
“…This localized distribution in the hypothalamus is significant as it aligns with the proposed effects of SEM in the brain, such as neuroprotection. These effects are believed to be associated with the interaction of SEM with GLP-1 receptors in the brain [ 64 , 65 , 66 , 67 , 68 ]. This paradoxical finding underscores the complexity of SEM’s interaction with the brain and challenges the conventional understanding of its BBB permeability.…”
Section: Sem Pharmacokinetics In Animal Modelsmentioning
confidence: 99%
“…Furthermore, Jung et al (2020) delved into the role of GLP‐1 in autophagy regulation within the context of insulin resistance 10 . Findings indicated that GLP‐1 receptor activation facilitated autophagy, offering a potential mechanism by which GLP‐1 agonists could alleviate insulin resistance, a hallmark of T2DM 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, Jung et al (2020) delved into the role of GLP-1 in autophagy regulation within the context of insulin resistance. 10 Findings indicated that GLP-1 receptor activation facilitated autophagy, offering a potential mechanism by which GLP-1 agonists could alleviate insulin resistance, a hallmark of T2DM. 10 By influencing autophagy, GLP-1 receptor agonists may contribute to the preservation of islet β cells, thereby improving insulin secretion and cellular survival.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations